Gray matter alteration in heroin-dependent men: An atlas-based magnetic resonance imaging study. (30th October 2020) - Shi, Hong; Liang, Zifei; Chen, Jiajie; Li, Wei; Zhu, Jia; Li, Yongbin; Ye, Jianjun; Zhang, Jiangyang; Xue, Jiuhua; Liu, Wei; Wang, Fan; Wang, Wei; et al.
Highlights: The characteristics of gray matter volume of heroin dependent (HD) men were analyzed with an atlas-based approach. The HD group showed lower cortical volume in prefrontal cortex and mesolimbic dopaminergic regions than healthy controls (HC). The HD group showed greater cortical volume in several visual and somatosensory cortical regions than HC group. The duration of heroin use was negatively correlated with the gray matter volume of prefrontal cortex. Abstract: Previous imaging studies on heroin addiction have reported brain morphological alterations. However, the effects of heroin exposure on gray matter volume varied among different studies due to different factors such as substitution treatment or mandatory abstinence. Meanwhile, the relationship between gray matter and heroin use history remains unknown. Thirty-three male heroin-dependent (HD) individuals who are not under any substitution treatment or mandatory abstinence and 40 male healthy controls (HC) were included in this structural magnetic resonance imaging study. With an atlas-based approach, gray matter structures up to individual functional area were delineated, and the differences in their volumes between the HD and HC groups were analyzed. In addition, the relationship between gray matter volume and duration of heroin use was explored. The HD group demonstrated significantly lower cortical volume mainly in the prefrontal cortex and mesolimbic dopaminergic regions across different parcellation levels, whereas several visual and somatosensory cortical regions in the HD group had greater volume relative to the HC group at a more detailed parcellation level. The duration of heroin use was negatively correlated with the gray matter volume of prefrontal cortex. These findings suggest that heroin addiction be related to gray matter alteration and might be related to damage/maladaption of the inhibitory control, reward, visual, and somatosensory functions of the brain, although cognitive correlates are warranted in future study. In addition, the atlas-based morphology analysis is a potential tool to help researchers search biomarkers of heroin addiction.